Empirical prediction of blast-induced vibration on adjacent tunnels - Li, Wenxin; Wang, Xiao; Chen, Lianjun; Wang, Chunguang; Liu, Jinxiao (Frontiers in Ecology and Evolution, 2023)
The blast-induced vibration during excavation by drilling and blasting method has an important impact on the surrounding buildings/structures and auxiliary equipment. In particular, with the development of tunnel engineering, the impact of blasting vibration on tunnel construction has attracted extensive attention. Based on literature data statistics, this paper first explored the performance of several common used empirical equations in predicting the propagation and attenuation characteristics of blasting vibration on adjacent tunnels; Secondly, the relationships between the empirical parameters of blasting vibration prediction equation and the geological strength index (GSI) of tunnel surrounding rock were discussed, and two new blasting vibration prediction equations based on site rock GSI were established to approximate predicting blast-induced vibration on adjacent tunnels; Finally, the application feasibility of the established prediction equation in practical engineering was discussed based on filed test data. The research result show that under the condition of multiple groups of data, the prediction performance of various prediction models is not differ significantly. With the increase of the GSI of the surrounding rock mass of the adjacent tunnel, the site coefficient β and k of blasting vibration prediction equation provided by Ambraseys and Hendron (1968) in predicting PPV (peak particle velocity, resultant velocity) are both show a decrease trend in whole. The site coefficient k is generally within 3000. Two new empirical prediction equations of blasting vibration propagation and attenuation on adjacent tunnels under different site conditions were established, as equation (14) for PPV and (15) for PPVi (max) (maximum value of the three component velocities; i = x, y, z represent peak component particle velocity). The verification analysis of five sites shows that these two equations have a certain practical application value. Compared with other empirical equations, these two equations do not need regression fitting blasting vibration data, only used the GSI of the site rock mass, they are more easy to use in field when lack of monitoring data.